# Algebra 1 - Solve for Unknown

Use the PEMDAS order of operations to simplify the following equation, combine like terms, and then solve for the unknown.

8m - (8 - m) = 28

### Comments for Algebra 1 - Solve for Unknown

 Sep 05, 2011 Equation - Solve for Unknown by: Staff The question: 8m - (8 - m) = 28 The answer: Simplify each side of the equation to the maximum extent: 8m - (8 - m) = 28 1. You should use the PEMDAS order of operations for the simplification process. PEMDAS order tells you what to do first, second, . . . etc. PEMDAS stands for: parentheses, exponents, multiplication, division, addition, subtraction Step 1: you should evaluate the expression inside each set of PARENTHESES PEMDAS order of evaluation: PARENTHESES, exponents, multiplication, division, addition, subtraction There is one expression enclosed in parentheses: (8 - m) This expression (inside the parentheses) cannot be simplified further. For the moment, it will remain (8 - m) Step 2: evaluate EXPONENTS PEMDAS order of evaluation: parentheses, EXPONENTS, multiplication, division, addition, subtraction There are no exponents to evaluate. Step 3: MULTIPLICATION PEMDAS order of evaluation: parentheses, exponents, MULTIPLICATION, division, addition, subtraction 8m - (8 - m) = 28 There is one place where you should complete the multiplication now: - (8 - m) = (-1) * (8 - m) = (-1) * (8) + (-1) * (-m) = -8 + m After completing the multiplication, the equation should look like this: 8m - 8 + m = 28 Step 4: DIVISION PEMDAS order of evaluation: parentheses, exponents, multiplication, DIVISION, addition, subtraction No division is necessary to simplify either side of the equation. However, you will use division to solve for the final value of m. Step 5: evaluate ADDITION & SUBTRACTION PEMDAS order of evaluation: parentheses, exponents, multiplication, division, ADDITION, SUBTRACTION You can combine like terms on the left side of the equation now: 8m - 8 + m = 28 8m + m - 8 = 28 9m - 8 = 28 At this point, you have used the PEMDAS order of operations to simplify the expression on each side of the equation to the maximum extent possible. 2. You can now solve for the final value of m. To eliminate the -8 from the left side of the equation, add 8 to each side of the equation: 9m - 8 + 8 = 28 + 8 9m + 0 = 28 + 8 9m = 28 + 8 9m = 36 To eliminate the 9 from the left side of the equation, divide each side of the equation by 9: 9m = 36 9m/9 = 36/9 m*(9/9) = 36/9 m*(1) = 36/9 m = 36/9 m = 4 the final answer is: m = 4 check the solution by substituting the numerical value of m into the original equation for m = 4 8m - (8 - m) = 28 8 * 4 - (8 - 4) = 28 32 - (8 - 4) = 28 32 - (4) = 28 32 - 4 = 28 28 = 28, OK → m = 4 is a valid solution Thanks for writing. Staff www.solving-math-problems.com

 Sep 14, 2017 hard NEW by: jem what is 13% of 540?

 Mar 07, 2019 simplify and solve for the unknown NEW by: Anonymous 2(2X+1)=2(x+4)